Contribution of information and communication technology in improving access to market information among smallholder farmers: The case study of Kilosa District - C. Njelekela; C. Sanga (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
This study investigates the contribution of information and communication technology in improving access to market information among smallholder farmers. The study was conducted at Kilosa District. The representative sample involved 50 smallholder farmers from two villages. A structured questionnaire was used to collect relevant information from random selected respondents. Data were analysed using statistical software. The overall findings revealed that there were great disparities in gender division of labour at the market process. Men participate much in access market information because they are the one who made decision. In other hand, women were performing more activities in the farm production compared to men who engaged themselves in market. The research concludes that there is unequal gender division of labour in the farm activities and also, on the access and use of the market information. Based on this, it is recommended that massive education campaign for mainstreaming gender is needed to both men and women who are actively engaged in smallholder farmers.
Keywords: 650; ICT; agriculture; market information; smallholder farmers